Human placenta-derived mesenchymal stem cells stimulate neuronal regeneration by promoting axon growth and restoring neuronal activity - de Laorden, Elvira H.; Simón, Diana; Milla, Santiago; Portela-Lomba, María; Mellén, Marian; Sierra, Javier; de la Villa, Pedro; Moreno-Flores, María Teresa; Iglesias, Maite (Frontiers in Cell and Developmental Biology, 2023)
In the last decades, mesenchymal stem cells (MSCs) have become the cornerstone of cellular therapy due to their unique characteristics. Specifically human placenta-derived mesenchymal stem cells (hPMSCs) are highlighted for their unique features, including ease to isolate, non-invasive techniques for large scale cell production, significant immunomodulatory capacity, and a high ability to migrate to injuries. Researchers are exploring innovative techniques to overcome the low regenerative capacity of Central Nervous System (CNS) neurons, with one promising avenue being the development of tailored mesenchymal stem cell therapies capable of promoting neural repair and recovery. In this context, we have evaluated hPMSCs as candidates for CNS lesion regeneration using a skillful co-culture model system. Indeed, we have demonstrated the hPMSCs ability to stimulate damaged rat-retina neurons regeneration by promoting axon growth and restoring neuronal activity both under normoxia and hypoxia conditions. With our model we have obtained neuronal regeneration values of 10-12% and axonal length per neuron rates of 19.99±0.77, μm/neuron. To assess whether the regenerative capabilities of hPMSCs are contact-dependent effects or it is mediated through paracrine mechanisms, we carried out Transwell co-culture and conditioned medium experiments confirming the role of secreted factors in axonal regeneration. It was found that hPMSCs produce brain derived, nerve- growth factors (BDNF, NGF) and Neurotrophin-3, involved in the process of neuronal regeneration and restoration of the physiological activity of neurons. In effect, we confirmed the success of our treatment using the patch clamp technique to study ionic currents in individual isolated living cells demonstrating that in our model the regenerated neurons are electrophysiologically active, firing action potentials. The outcomes of our neuronal regeneration studies, combined with the axon-regenerating capabilities exhibited by mesenchymal stem cells derived from the placenta, present a hopeful outlook for the potential therapeutic application of hPMSCs in the treatment of neurological disorders.